Educação infantil: a construção do número em atividades contidas em um livro didático de matemática - Fernandes, Eunice Ramos de Carvalho (2017)
The present research aims to analyze if the mathematical activities contained in Buriti Mirim's collection of textbooks of Editora Moderna, directed to Early Childhood Education, provide the construction of the number for young children. As specific objectives, we highlight the following: the book has classification, serialization and ordering activities since they are fundamental for number construction, observing how the class teacher uses this instrument and observing what strategies the children use to carry out the activities. The research was conducted in the last cycle of a private school of Early Childhood Education located in the city of São Paulo which adopts the material in question and the subjects were seven children aged five years and a teacher. We used a qualitative methodological approach and, as an instrument of data collection, we made use of participant observation. The analysis of the data was based on the proposal of content analysis of Bardin. As a theoretical reference, we will betake the following authors: Piaget (2013), Kamii (2012), Ramos (2009) to substantiate the number construction category; Barbosa (2009), Campos (2005), Campos et al. 2011), Oliveira (2010) to support the category early childhood education; Gomes and Magalhães (2012), D'Ambrosio (2005, 2012), Zorzan (2007) Skovsmose (2013) to base the category mathematics. We also analyzed some documents that rules Early Childhood Education. As a result, we find out that the book has concerns about working with children and not just records of activities. It contributes to the teaching of the National Curricular Reference Framework for Early Childhood Education (RCNEI), although many activities starts with the teacher and not with the child as the protagonist. Some activities have an end in itself. The playful is part of the universe of children and, in general, helps the development of logical-mathematical reasoning, favoring the construction of numbers. The book's activities works only as a resource for the teacher and not as an indispensable tool.